Molecular diagnosis of urogenital schistosomiasis in pre-school children, school-aged children and women of reproductive age at community level in central Senegal - Doudou Sow; Khadime Sylla; Ndeye Marème Dieng; Bruno Senghor; Papa Mouhamadou Gaye; Cheikh B. Fall; Ndiaw Goumballa; Aldiouma Diallo; Jean Louis A. Ndiaye; Philippe Parola; Cheikh Sokhna; Souleymane Doucouré; et al. (Parasites & Vectors, 2023)
Abstract Background Urogenital schistosomiasis is a major public health concern in sub-Saharan Africa. In Senegal, the disease is endemic in all regions of the country. Recently, WHO strongly recommended including pre-school children and women of reproductive age during a mass drug administration campaign. It is important to describe the burden of the disease in these group at risk using innovative diagnostic tools. This study aimed to assess the use of real-time PCR in the detection of schistosomiasis cases at the community level in a seasonal transmission area. Methods A cross-sectional survey was carried out in Niakhar located in the centre of Senegal. Pre-schoolchildren, school-aged children and female adolescents and adults were invited to participate in the study in April 2018. Urine samples were collected and examined using Hemastix reagent strips, filtration technique and real-time PCR. Schistosoma haematobium was detected, identified by targeting the Dra1 gene. The prevalence of urogenital schistosomiasis was determined for each group and the performance of the real-time PCR was compared with the conventional techniques. Results A total of 428 participants were enrolled in this study including 87 (20.4%) pre-school children (1–5 years), 262 (61.3%) school-aged children between (5–14 years), 17 (3.9%) adolescents (15–17 years) and 62 (14.4%) female adults. The comparison of the diagnostic techniques has shown that the prevalence of urogenital schistosomiasis is higher using molecular technique (34.6%) compared to microscopy (20.3%). The percentage rate of haematuria using Hemastix was 23.1%. School-aged children between 5 and 14 years old were the most affected with 29.0% and 43.1% under microscopy and RT-PCR, respectively. In female participants, microscopic prevalence decreases with age, from 21.4% in school-aged children to 17.6% in adolescents and 9.7% in adults. There was good correlation between the number of eggs per 10 ml and the cycle threshold range. Conclusion These results show the importance of using molecular tools in the surveillance of schistosomiasis particularly in pre-school children and women of reproductive age. Graphical Abstract